Synthesis method of two translational compliant mechanisms with redundant actuation - S. Li (Copernicus Publications, 2021)
In the fields of electronic packaging, micromanipulation, scanning, and two translational (2T) mechanisms are required, especially with high stiffness, for a large workspace, with good driving stability, and other occasions. Redundant actuators are required to improve the performance of the 2T compliant parallel mechanism. The novelty of the work is to propose a new method for the type synthesis of a 2T redundant actuated compliant parallel mechanism based on the freedom and constraint topology (FACT) approach and the atlas approach. The synthesis conditions are given, and the synthesis process is formulated. With this method, new 2T redundant actuated compliant parallel mechanisms are synthesized. Some new mechanisms have been synthesized, which enriches the compliant parallel mechanism configurations. Based on the atlas method, the synthesized mechanism is analyzed. The results verify the correctness and effective of the synthesis method. The method is also suitable for a type of synthesis of redundant actuated compliant parallel mechanisms with 3, 4, 5, and 6 degrees of freedom (DOF), respectively.